2011
DOI: 10.1103/physrevlett.107.047003
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructed Fermi Surface of UnderdopedBi2Sr2CaCu2O8+δCuprate Superconductors

Abstract: The Fermi surface topologies of underdoped samples of the high-T(c) superconductor Bi2Sr2CaCu2O(8+δ) have been measured with angle resolved photoemission. By examining thermally excited states above the Fermi level, we show that the observed Fermi surfaces in the pseudogap phase are actually components of fully enclosed hole pockets. The spectral weight of these pockets is vanishingly small at the magnetic zone boundary, creating the illusion of Fermi "arcs." The area of the pockets as measured in this study i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
136
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(153 citation statements)
references
References 25 publications
15
136
2
Order By: Relevance
“…13 The same ansatz is consistent with the crossover from arcs to full Fermi surface observed in the SISTM studies and has also recently been shown to be consistent with the doping dependence observed for the carrier density in quantum oscillation studies. 37 Embedded within the YRZ phenomenology is a self-energy term associated with the doping dependent pseudogap,…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…13 The same ansatz is consistent with the crossover from arcs to full Fermi surface observed in the SISTM studies and has also recently been shown to be consistent with the doping dependence observed for the carrier density in quantum oscillation studies. 37 Embedded within the YRZ phenomenology is a self-energy term associated with the doping dependent pseudogap,…”
Section: Introductionsupporting
confidence: 74%
“…Several studies have been interpreted as indicating a temperature dependent arc length, 10 others a doping dependent length. 11,12 More detailed studies have suggested that the arcs do, in fact, represent one side of an asymmetric hole-pocket 13 consistent with several models of the doped Mott insulator at low doping. 14,15,16 As a function of increased doping, the hole pockets grow with an area proportional to x, the doping level, until, at some critical doping level, the pockets switch to the full Fermi surface, associated with a more metallic state, as the pseudogap disappears.…”
Section: Introductionmentioning
confidence: 84%
“…3(g), near the tip of the Fermi arc the band dispersion is not particle-hole symmetric but simply turns around and loses spectral weight. This feature has been emphasized by Yang et al [36] in their data, which they interpreted using a phenomenological model by Yang et al [37]. A second unusual feature of the data of Ref.…”
mentioning
confidence: 75%
“…In particular, the CDW model predicts a large gap below the Fermi level at the end of the Fermi arc, which has never been seen experimentally. In fact, it has been emphasized that a gap exists above the Fermi level near the end of the Fermi arc [36]. We note that Ref.…”
Section: Appendix A: Incompatibility Of the Cdw Model With The Arpes mentioning
confidence: 99%
“…This was motivated by the need to reconcile transport experiments [13][14][15][16] and photoemission data [17][18][19] in the underdoped region of cuprate superconductors: while photoemission data show Fermi arcs enclosing an area 1 + p (with p being the doping), transport measurements indicate plain Fermi-liquid properties consistent with an area p. In order to resolve this issue and produce a Fermi liquid which encloses an area p, the authors of Refs. [10][11][12] introduced a model for the pseudogap region of the cuprate superconductors which consists of two types of dimers: one spinless bosonic dimer -representing a valence bond between two neighboring spins -and one spin 1/2 fermionic dimer representing a hole delocalized between two sites.…”
Section: Introductionmentioning
confidence: 99%